Physical and performance differences among forwards, defensemen, and goalies in elite women's ice hockey - Geithner, C. A.; Lee, A. L.; Bracko, M. R. (The Journal of Strength and Conditioning Research, 2006)
Positional differences have been examined in women's basketball, field hockey, netball, and volleyball, but not in elite women's ice hockey. Our purpose was to describe and compare physical, fitness, and skating performance characteristics of forwards (F), defensemen (D), and goalies (G). Subjects were 112 University of Alberta women players (21.4 ± 2.9 years of age). A full anthropometric battery was conducted on each player. Heath-Carter anthropometric somatotypes were calculated. Percent body fat (%fat) was estimated from both general and population-specific equations. Subjects performed off-ice fitness tests (vertical jump, 40-yd dash, Leger test for predicting O2max) and on-ice fitness (Modified 3-Repeat Sprint Skate Test—MRSS, blood lactate after sprint test) and skating performance tests (6.10-m acceleration test, Cornering S-Turn Agility Test). Descriptive statistics and multivariate analyses of variance were run using SPSS (Version 10.0) for the MacIntosh, with a significance level set a priori at p < 0.05. Significant positional differences were found for bicristal breadths (D > G, F > G); relaxed arm circumference (D > F, G > F); supraspinale and biceps skinfolds (G > D, G > F); and endomorphy (G > F). Significant differences among positions were also found for the MRSS (G > D > F) and agility tests (G > D, G > F). D tended to have the most robust build overall. F were leaner than D and G, and their smaller relaxed arm circumference measurements most likely reflect less subcutaneous fat on the upper arm. F had greater anaerobic power than D, followed by G, and they tended to have greater aerobic capacity. F and D were more agile than G. Performance demands appear to be position specific. F need to be the most versatile and fit because of a greater amount and variety of work performed both during practices and games; their required degrees of versatility and fitness are followed by those required of D and G.